Utilization of Immersive Technology in Qualitative Research Design: Virtual Reality (VR) and Augmented Reality (AR) Opportunities - Muhammad Rahmad; Willy Arafah; Rahmat Ingkadijaya; Hera Oktadiana (Jurnal Indonesia Sosial Teknologi, 2024)
This study examines the potential use of immersive technology, especially Virtual Reality (VR) and Augmented Reality (AR), in qualitative research design. As technology advances, VR and AR open up new opportunities to improve the quality and depth of data collection and analysis in qualitative research. Through a systematic literature review and case studies, this study explores various applications of immersive technology in the context of qualitative research, including environmental simulations for observation, immersive interviews, and analysis of enriched visual data. The findings suggest that VR and AR can increase participant engagement, expand the reach of data collection, and provide a new perspective in the analysis of social phenomena. However, the study also identifies ethical and methodological challenges that need to be addressed, such as data privacy issues and the validity of results in a virtual environment. The study concludes that the integration of immersive technologies in qualitative research has significant potential to enrich research methodologies while emphasizing the importance of a careful and ethical approach in its implementation. The implications for the development of qualitative research methodologies in the digital era are also discussed.